2004
DOI: 10.17221/5731-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

A survey of attitudes of Turkish veterinary students and educators about animal use in research

Abstract: ABSTRACT:In this study, veterinary students and veterinary educators from Firat Veterinary School, Istanbul Veterinary School and Selcuk Veterinary School were surveyed to evaluate their a�itudes to animal use in research. Data were collected from 330 students and 204 educators by personal interviews. All participants showed anthropocentric a�itudes toward animal use in research. Most of the participants agreed on items regarding the animal tests being easier, more scientific, more common, more economical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
1
0
4
Order By: Relevance
“…In another study, Navvaro, Maldonado, Pedraza, and Cavas (2001) stated that 65.7% of the psychology students participating in their study support animal experiments. In their study on veterinary faculty students and academicians, Yerlikaya et al (2004) found that the participants are of the opinion that animal experiments are cheaper, more reliable and more scientific than alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Navvaro, Maldonado, Pedraza, and Cavas (2001) stated that 65.7% of the psychology students participating in their study support animal experiments. In their study on veterinary faculty students and academicians, Yerlikaya et al (2004) found that the participants are of the opinion that animal experiments are cheaper, more reliable and more scientific than alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…[18] , Avustralya ve Türkiye'deki veteriner fakültesi öğrencileri üzerinde yaptıkları bir çalışmada hayvanların deneylerde kullanılmasına genelde nötr bir yaklaşım olduğunu, ancak Türkiye'deki öğrencilerin hayvan kullanımında daha "kabul edilebilir" bir tutum sergilediklerini; Yerlikaya ve ark. [15] ile Özen ve Özen [16,17] veteriner fakültesi öğrencileri ile akademisyenlerinin alternatif yön-temlerin deney hayvanı kullanımına oranla pek çok yön-den avantajlı olduğuna dair görüş bildirdiklerini belirlemişlerdir. Çalışmada, bilimsel araştırmalarda hayvan kullanımının zorunluluğu konusundaki tutumun yüksek olduğu (%69.2, n=144) ve çalışılan alan/mezun olunan fakülte değişkeni bakımından istatistikî açıdan anlamlı bir fark olduğu (P=0.01); alternatif yöntemler yerine deney hayvanı kullanımı konusunda Yerlikaya ve ark.…”
Section: Tartişma Ve Sonuçunclassified
“…Çalışmada, bilimsel araştırmalarda hayvan kullanımının zorunluluğu konusundaki tutumun yüksek olduğu (%69.2, n=144) ve çalışılan alan/mezun olunan fakülte değişkeni bakımından istatistikî açıdan anlamlı bir fark olduğu (P=0.01); alternatif yöntemler yerine deney hayvanı kullanımı konusunda Yerlikaya ve ark. [15] ile Özen ve Özen'e [16,17] paralel olarak negatif bir tutumun olduğu (%44.7, n=93) tespit edildi. Bununla birlikte il ile eği-tim durumu yönünden istatistikî açıdan önemli bir fark olması (P=0.000 ve P=0.035) (Tablo 2) hayvan deneylerinin zorunluluğuna ilişkin genel görüşe rağmen, araştır-macıların aldıkları eğitim ve çalıştıkları alanın etkisiyle, alternatif seçenekleri de göz önünde tutma yönünde bir eğilim gösterdikleri şeklinde değerlendirilebilir.…”
Section: Tartişma Ve Sonuçunclassified
See 2 more Smart Citations